1996
DOI: 10.1021/ci950121w
|View full text |Cite
|
Sign up to set email alerts
|

“The Mole Environment”Development and Implementation of Studyware

Abstract: The mole is a fundamental concept in chemistry. It is a basic measurement unit and is used for stoichiometric calculations, expressing solution concentrations, equilibrium constant, and pH. Many students have difficulties in understanding and applying the mole concept. Students therefore adopt a variety of algorithmic techniques for solving problems provided as predefined templates in books, classes, tests, and matriculation examinations. Consequently, some of the students are not capable of solving complicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The development of the studyware was based on the previous studies and recommendations in the fields of software and chemical and environmental education (Dori & Hameiri, 1996.…”
Section: Mole Environment Studywarementioning
confidence: 99%
“…The development of the studyware was based on the previous studies and recommendations in the fields of software and chemical and environmental education (Dori & Hameiri, 1996.…”
Section: Mole Environment Studywarementioning
confidence: 99%
“…Nevertheless we were able to prove that Examination Boards in Britain and the Netherlands chose sensible distractors in their multiple choice questions about stoichiometry (Schmidt, 1990(a)). Recently, the results of our research have been used to develop learning pro~ams about stoichiometric calculation (Dori & Hameiri, 1996). In order to find out the strategies that students use outside Germany our test questions have to be tested abroad-not too difficult a task to tackle.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also considered the potential of computers to assist in the teaching of the mole (Bilgin & Kirike, ; Dori, ; Green & Flinders, ; Nakhleh & Krajcik, ; Yalcinalp, Geban, & Ozkan, ). The Mole Environment by Dori and Hameiri (, ) is an example. This program incorporated mole‐related problems at several cognitive levels that progressed in difficulty and complexity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This program incorporated mole‐related problems at several cognitive levels that progressed in difficulty and complexity. By comparing the results from a pretest and posttest, Dori and Hameiri () found that using this program to practice mole‐related problems could improve learners' understandings of the mole. Both the approach by Rowell and Dawson () and the computer programs focused on training students to solve stoichiometric problems.…”
Section: Literature Reviewmentioning
confidence: 99%